Investigations into the dyeing industry in Pompeii experimental archaeology and computer simulation techniques. - Pepper, Heather Hopkins (Archaeopress Roman archaeology, 2021)
The scale of processing associated with the dyeing industry in Pompeii is a controversial subject. This investigation uses a new multi-disciplinary triangulated approach, providing an understanding of the significance of the industry that is grounded in engineering and archaeological principles, but within the context of Pompeii.